2021
DOI: 10.1186/s12877-021-02142-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of frailty and associated factors among Saudi community-dwelling older adults: a cross-sectional study

Abstract: Background Prevalence of frailty has been previously established in different Western countries; however, the prevalence and the burden of in the aging populations of Saudi Arabia has not been examined. Therefore, the aim of this study was to examine the prevalence of frailty, and associated factors among Saudi older population. Methods The study included a total of 486 community-dwelling elderly adults aged 60 years and over living in the Riyadh a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 42 publications
(25 reference statements)
3
17
3
Order By: Relevance
“…This study also highlights our study’s results, indicating that the prevalence of frailty in people aged 60 years or older in our cohort is 58.1%. This is higher compared to the previous study among Saudi community-dwelling older adults [ 31 ]. On the other hand, the finding is similar to a study conducted in Cuba that found that the prevalence rate of 51% in the elderly [ 32 ].…”
Section: Discussioncontrasting
confidence: 69%
“…This study also highlights our study’s results, indicating that the prevalence of frailty in people aged 60 years or older in our cohort is 58.1%. This is higher compared to the previous study among Saudi community-dwelling older adults [ 31 ]. On the other hand, the finding is similar to a study conducted in Cuba that found that the prevalence rate of 51% in the elderly [ 32 ].…”
Section: Discussioncontrasting
confidence: 69%
“…This study was part of a previous project where measurements of sleep was collected on a subsample of the original study sample. An explanation of the sampling and recruitment methods of the original sample can be found elsewhere [ 11 ]. Detail about participants’ enrollment is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…According to a meta-analysis of research from various populations, frailty prevalence ranged from 4% to 51% in China and Cuba, respectively [ 10 ]. In addition, a recent research reported 21% prevalence of frailty among older adults in Saudi Arabia [ 11 , 12 , 13 ]. Furthermore, research suggests that frailty is a dynamic condition and may be controlled and prevented by treatments, such as health promotion, diet, physical activity, and social engagement [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of all of the included studies ranged from 3 to 8 as per the Newcastle-Ottawa scale with a mean score of 6.18 for all included studies indicating satisfactory quality. One study scored 3 [ 17 ] two studies scored 5 [ 16 , 27 ] two studies scored 6 [ 23 , 24 ] five studies scored 7 [ 15 , 19 , 25 , 26 ] and one study scored 8 [ 20 ] No studies scored 1, 2, 4 or 9. Table 2 shows the quality rating for all included studies.…”
Section: Resultsmentioning
confidence: 99%